Genesis, properties, classification and assessment of soils in Central Benin, West Africa - Junge, B.; Skowronek, A. (Elsevier, 2007)
The sustainable use of the soil resource requires extensive knowledge about its genesis, morphology, and properties. Consequently, soil data are basis for improved land use management and soil conservation. The present study illustrates morphology and physical, chemical and mineralogical properties of the soils developed in the pediplain of Central Benin. The pediments are characterized by different substrate layers, whereas the material of valleys and the surroundings of inselbergs are of colluvial origin. Termites also play an important role in tropical soils by influencing soil properties. Movement of clay and sesquioxides are typical pedogenetic processes, resulting in the formation of horizons enriched with clay or of ferricrete. The soils of the study site are classified as Sols ferrugineux tropicaux lessivés, Sols hydromorphes, Sols minéraux bruts, and Sols bruns, according to the French Classification des Sols, as Alfisols, Inceptisols, or Entisols according to the U.S.D.A. Soil Taxonomy, or as Acrisols, Plinthosols, Gleysols, Fluvisols, Leptsols, and Cambisols according to the classification systems of the FAO-UNESCO legend and the World Reference Base for Soil Resources. The assessment of soil shows that the fertility of the pediment soils is generally low due to the low amount of organic matter, nutrients and poor water holding capacity of the sandy topsoil. The loamy soils surrounding the inselberg as well as the areas influenced by termites are more fertile because of a higher amount of nutrients and better water holding capacity.